1990
DOI: 10.1152/jappl.1990.68.5.2067
|View full text |Cite
|
Sign up to set email alerts
|

Glucoregulation and hormonal responses to maximal exercise in non-insulin-dependent diabetes

Abstract: Maximal dynamic exercise results in a postexercise hyperglycemia in healthy young subjects. We investigated the influence of maximal exercise on glucoregulation in non-insulin-dependent diabetic subjects (NIDDM). Seven NIDDM and seven healthy control males bicycled 7 min at 60% of their maximal O2 consumption (VO2max), 3 min at 100% VO2max, and 2 min at 110% VO2max. In both groups, glucose production (Ra) increased more with exercise than did glucose uptake (Rd) and, accordingly, plasma glucose increased. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
112
4
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 0 publications
15
112
4
6
Order By: Relevance
“…Studies also show lower VO 2max in type 2 diabetic patients compared with age-matched nondiabetic control subjects (22,60,61). The current study showed that the peak VO 2max in type 2 diabetic subjects with poor glycemic control was lower than weight-matched control subjects, although insulin treatment did not significantly alter this.…”
Section: Discussionsupporting
confidence: 40%
“…Studies also show lower VO 2max in type 2 diabetic patients compared with age-matched nondiabetic control subjects (22,60,61). The current study showed that the peak VO 2max in type 2 diabetic subjects with poor glycemic control was lower than weight-matched control subjects, although insulin treatment did not significantly alter this.…”
Section: Discussionsupporting
confidence: 40%
“…An enhanced post-exercise insulin sensitivity has been demonstrated both for glucose-tolerant individuals and for various insulin-resistant populations, including patients with type 2 diabetes, with the change mainly accounted for by an increase in NOGD [11][12][13]. As glycogen synthesis is the primary pathway of NOGD [1], these changes favour glycogen replenishment after exercise [13,17,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In the postprandial state, exercise has been demonstrated not to increase HGP in hyperinsulinemic patients with type 2 diabetes (11). In contrast, other studies found similar increases in HGP in patients with type 2 diabetes and in healthy control subjects during moderateintensity exercise (12,13).…”
mentioning
confidence: 81%